Impersonation : a novel - Pitlor, Heidi (Algonquin Books of Chapel Hill, 2020)
"Allie Lang is a professional ghostwriter and a perpetually broke single mother to a young boy. Years of navigating her own and America's cultural definitions of motherhood have left her a lapsed idealist. Lana Breban is a powerhouse lawyer, economist, and advocate for women's rights with designs on elected office. She also has a son. Lana and her staff have decided she needs help softening her public image and that a memoir about her life as a mother will help. When Allie lands the job as Lana's ghostwriter, it seems as if things will finally go Allie's way. At last, she thinks, there will be enough money not just to pay her bills but to actually buy a house. After years of working as a ghostwriter for other celebrities, Allie believes she knows the drill: she has learned how to inhabit the lives of others and tell their stories better than they can. But this time, everything becomes more complicated. Allie's childcare arrangements unravel; she falls behind on her rent; her subject, Lana, is better at critiquing than actually providing material; and Allie's boyfriend decides to go on a road trip toward self-discovery. But as a writer for hire, Allie has gotten too used to being accommodating. At what point will she speak up for all that she deserves?"--Provided by publisher.